Multi-criteria decision making for selecting wastewater treatment technology using fuzzy analytic hierarchy process - Orbecido, Aileen H. (Animo Repository, 2013)
The selection of the appropriate technology requires the assessment and evaluation of multiple criteria which may be qualitative and/or quantitative in nature. The decision maker needs to take into consideration the performance of technology alternatives in each criterion and evaluate as well the relative importance of these criteria towards teh over-all objective. Fuzzy Analytic Hierarchy Process (FAHP) is thus utilized in this work to structure the selection problem systematically and to conduct the selection more rationally. It allows the decision-maker to express not only his expert judgment but also the associated level of confidence he has on these judgments through pairwise comparisons between criteria and between alternatives. The methodology is demonstrated utilizing a case study on the comparison of wastewater treatment options for municipal wastewater.